2022
DOI: 10.3390/jof8020172
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Barley (Hordeum vulgare) with the Endophyte Epichloë bromicola Affects Plant Growth, and the Microbial Community in Roots and Rhizosphere Soil

Abstract: Hordeum vulgare is an important source of feed and forage for livestock, and of food and drink for humans, but its utilization rate is lower than that of other cereal crops, thus it is crucial to improve barley agronomic traits and production. Epichloë bromicola is an endophyte that was isolated from wild barley (Hordeum brevisubulatum). Previous studies have found that Epichloë can indirectly influence the growth of host plants by affecting soil chemical characteristics, the microbial community, and by produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
1
5
0
Order By: Relevance
“…However, studies have shown that dominant endophytic fungi can have huge ecological consequences, and some studies have shown that endophytic fungi can affect the expression of host genes and thus affect plants ( Harrison et al, 2021 ). In addition, the results of Liu et al (2022) showed that the endophytic fungus Epichloë bromicola can affect the growth of host plants and has a significant effect on the plant height of Hordeum vulgare . Therefore, it can be hypothesized that the formation of round AOJs and triangular AOJs may be due to the existence of some endophytic fungi that affect the gene expression or growth of AOJs, and these endophytes are different in AOJ plants with two traits, which are reflected in the significant difference in ASVs and the difference in dominant genera.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that dominant endophytic fungi can have huge ecological consequences, and some studies have shown that endophytic fungi can affect the expression of host genes and thus affect plants ( Harrison et al, 2021 ). In addition, the results of Liu et al (2022) showed that the endophytic fungus Epichloë bromicola can affect the growth of host plants and has a significant effect on the plant height of Hordeum vulgare . Therefore, it can be hypothesized that the formation of round AOJs and triangular AOJs may be due to the existence of some endophytic fungi that affect the gene expression or growth of AOJs, and these endophytes are different in AOJ plants with two traits, which are reflected in the significant difference in ASVs and the difference in dominant genera.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial inoculation results in profound increment of root surface area by eightfold as compared to uninoculated in barley [24]. Similarly, N-fixing rhizobacteria had a positive effect on above-ground biomass of maize and barley [44,27,45]. In both years, N and P treatments increased grain N content, physiological maturity N content, straw yield; sole N applications had the highest grain and plant N contents.…”
Section: Physiological Maturity Period Plant Protein Content (%)mentioning
confidence: 97%
“…Barley (Hordeum vulgare L.) is from the family Poaceae (Graminae); After wheat, maize, and rice, it is the fourth most common food cereal in the world [1,2]. It provides animals to feed, as well as human food and drink [3,4]. Barley-produced food is a good source of many nutrients, including protein with its high nutritional value, rich in protein 9.9 g, fibers, selenium, minerals, and B-vitamins.…”
Section: Introductionmentioning
confidence: 99%